Law Code as Plot Template in Biblical Narrative (1 Kings 9.26–11.13; Joshua 2.9–13) - Berman, Yehoshuʿa (Journal for the study of the Old Testament, 2016)
This article explores a particular fashion through which biblical narrative in the so-called Deuteronomistic History employs legal passages toward rhetorical ends: the narrative references a legal text and uses its language, laws and motifs as a template through which to compose a homiletic tale. Invoking a phrase from a legal passage, the text calls upon us to read the narrative in light of that passage as a whole. 1 Kings 9.26–11.13 engages the whole text of the law of the king (Deut. 17.14–20) to describe Solomon's downfall, in a more thorough way than has heretofore been recognized. Rahab's soliloquy in Josh. 2.9–13 employs a tight weave of references to the first commandments of the Decalogue, demonstrating that she is worthy of being spared. In each, the law is extracted from its original focus and emerges within a new configuration of meaning.